A microwell plate-based multiplex immunoassay for simultaneous quantitation of antibodies to infectious viruses - Jeong, Min-Suk; Ahn, Dae-Ro (Royal Society of Chemistry, 2015)
Antibodies (Abs) to disease-causing viruses in human blood are important indicators of infection status. While ELISA has been widely used to detect these Abs, a multiplex assay system for simultaneous detection of multiple Abs is still a desirable alternative method for a more efficient screening process because of the lack of multiplexing ability in ELISA. However, as all antibodies are based on immunoglobulin and recognized commonly by the same secondary antibody, it is impossible to multiplex the conventional indirect ELISA in a 96-microwell plate-based platform. To overcome this hurdle, we designed an assay consisting of two steps: capturing target Abs by specific antigens on DNA-encoded gold nanoparticles; and quantifying the target Abs by producing RNase H-mediated detection signals based on the DNA and additional RNA probes. With this newly designed method, we could simultaneously analyze three infectious disease-related Abs, anti-HIV Ab, anti-HCV Ab, and anti-HBV Ab, on the microwell-based platform. The assay performance was evaluated by comparison with ELISA. Furthermore, the accuracy and precision of the assay in a practical application was also estimated by determining the amount of target Abs in human serum solutions.
Keywords: HEPATITIS-C VIRUS; IMMUNOSORBENT-ASSAY; B-VIRUS; AMPLIFICATION; QUANTIFICATION; SYSTEM; REGION